Detection of Host-Derived Sphingosine by Pseudomonas aeruginosa Is Important for Survival in the Murine Lung - LaBauve, Annette E. (Public Library of Science, 2014)
Pseudomonas aeruginosa is a common environmental bacterium that is also a significant opportunistic pathogen, particularly of the human lung. We must understand how P. aeruginosa responds to the lung environment in order to identify the regulatory changes that bacteria use to establish and maintain infections. The P. aeruginosa response to pulmonary surfactant was used as a model to identify transcripts likely induced during lung infection. The most highly induced transcript in pulmonary surfactant, PA5325 (sphA), is regulated by an AraC-family transcription factor, PA5324 (SphR). We found that sphA was specifically induced by sphingosine in an SphR-dependent manner, and also via metabolism of sphingomyelin, ceramide, or sphingoshine-1-phosphate to sphingosine. These sphingolipids not only play a structural role in lipid membranes, but some are also intracellular and intercellular signaling molecules important in normal eukaryotic cell functions as well as orchestrating immune responses. The members of the SphR transcriptome were identified by microarray analyses, and DNA binding assays showed specific interaction of these promoters with SphR, which enabled us to determine the consensus SphR binding site. SphR binding to DNA was modified by sphingosine and we used labeled sphingosine to demonstrate direct binding of sphingosine by SphR. Deletion of sphR resulted in reduced bacterial survival during mouse lung infection. In vitro experiments show that deletion of sphR increases sensitivity to the antimicrobial effects of sphingosine which could, in part, explain the in vivo phenotype. This is the first identification of a sphingosine-responsive transcription factor in bacteria. We predict that SphR transcriptional regulation may be important in response to many sites of infection in eukaryotes and the presence of homologous transcription factors in other pathogens suggests that sphingosine detection is not limited to P. aeruginosa.